Glucose transporters and sodium glucose co-transporters cooperatively import glucose into energy-demanding organs in carcinogenic liver fluke Clonorchis sinensis. - Fuhong Dai; Soon-Ok Lee; Jin-Ho Song; Won-Gi Yoo; Eun-Hee Shin; Xuelian Bai; Sung-Jong Hong (Public Library of Science (PLoS), 2024)
Background The liver fluke Clonorchis sinensis imports large amounts of glucose to generate energy and metabolic intermediates through glycolysis. We hypothesized that C. sinensis absorbs glucose through glucose transporters and identified four subtypes of glucose transporter (CsGTP) and one sodium glucose co-transporter (CsSGLT) in C. sinensis. Methodology/principal findings Expressed sequence tags encoding CsGTPs were retrieved from the C. sinensis transcriptome database, and their full-length cDNA sequences were obtained by rapid amplification of cDNA ends (RACE). The tissue distribution of glucose transporters in C. sinensis adults was determined using immunohistochemical staining. Developmental expression was measured using RT-qPCR. The transport and distribution of glucose into living C. sinensis were monitored using confocal microscopy. Membrane topology and key functional residues of CsGTPs were homologous to their counterparts in animals and humans. CsGTP1, 2, and 4 were transcribed 2.4-5.5 times higher in the adults than metacercariae, while CsGTP3 was transcribed 2.1 times higher in the metacercariae than adults. CsSGLT transcription was 163.6 times higher in adults than in metacercariae. In adults, CsSGLT was most abundant in the tegument; CsGTP3 and CsSGLT were localized in the vitelline gland, uterine wall, eggs, mesenchymal tissue, and testes; CsGTP4 was found in sperm and mesenchymal tissue; and CsGTP1 was mainly in the sperm and testes. In C. sinensis adults, exogenous glucose is imported in a short time and is present mainly in the middle and posterior body, in which the somatic and reproductive organs are located. Of the exogenous glucose, 53.6% was imported through CsSGLT and 46.4% through CsGTPs. Exogenous glucose import was effectively inhibited by cytochalasin B and phlorizin. Conclusions/significance We propose that CsSGLT cooperates with CsGTPs to import exogenous glucose from the environmental bile, transport glucose across mesenchymal tissue cells, and finally supply energy-demanding organs in C. sinensis adults. Studies on glucose transporters may pave the way for the development of new anthelmintic drugs.